Gender Mainstreaming in Forest Fire Disaster Management Policy in Riau Province - Risdayati Risdayati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
As a social problem, the forest fire disaster in Riau Province requires a systematic response, such as through social policies. This article will discuss forest fire disaster management policies. The findings of this article indicate that disaster management policies should take a gender mainstreaming approach when developing policy frameworks and implementing them. In addition, effective policies require collaboration among disaster stakeholders.